2019
DOI: 10.1038/s41598-019-40452-6
|View full text |Cite
|
Sign up to set email alerts
|

Alignment-free method for DNA sequence clustering using Fuzzy integral similarity

Abstract: A larger amount of sequence data in private and public databases produced by next-generation sequencing put new challenges due to limitation associated with the alignment-based method for sequence comparison. So, there is a high need for faster sequence analysis algorithms. In this study, we developed an alignment-free algorithm for faster sequence analysis. The novelty of our approach is the inclusion of fuzzy integral with Markov chain for sequence analysis in the alignment-free model. The method estimate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…For example, Zhou et al constructed a complex network for similarity/dissimilarity analysis of DNA sequences [ 1 ]. Saw et al perform DNA sequence comparison using the fuzzy integral with Markov chain [ 2 ]. Lichtblau uses Frequency Chaos Game Representation and signal processing for genomic sequence comparison [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhou et al constructed a complex network for similarity/dissimilarity analysis of DNA sequences [ 1 ]. Saw et al perform DNA sequence comparison using the fuzzy integral with Markov chain [ 2 ]. Lichtblau uses Frequency Chaos Game Representation and signal processing for genomic sequence comparison [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…We represented the protein sequence as a set of material points in a 20D space [14]. Saw et al analyzed the similarity of DNA sequences using the fuzzy integral with a Markov chain [15]. Lichtblau applied frequency chaos game representation and signal processing for genomic sequence comparison [16].…”
Section: G G T T G G a A 2 G T G T G A G Amentioning
confidence: 99%
“…For the unaligned sequences, it is a way toward alignment-free approach of sequence comparison. A quite number of studies have shown the advantages of using alignment-free algorithms over alignment-base methods due to their computational limitations such as alignment errors and incongruences, whole genome comparison and etc (Susana and Jonas, 2003;Chan and Ragan, 2013;Zielezinski et al, 2017;Zielezinski et al, 2019;Saw, et al, 2019).…”
Section: Alignment Independencymentioning
confidence: 99%